2011
DOI: 10.1093/jac/dkr242
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tigecycline: a systematic review and meta-analysis

Abstract: In the light of the increased mortality, probably explained by decreased clinical and microbiological efficacy, clinicians should avoid tigecycline monotherapy in the treatment of severe infections and reserve it as a last-resort drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
151
1
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(168 citation statements)
references
References 47 publications
4
151
1
12
Order By: Relevance
“…Carbapenems are the most effective option for nosocomial infections in areas with a high prevalence of extended-spectrum β-lactamase-producing Enterobacteriaceae. Tigecycline may be a potential alternative, although recent studies have showed increased mortality related to its low clinical efficacy and it should not, therefore, be recommended as first-line therapy in the general population [58] . Penicillin used in combination with β-lactamase inhibitors (e.g., piperacilin-tazobactam) may be an adequate alternative.…”
Section: Treatment Of Nosocomial Sbpmentioning
confidence: 99%
“…Carbapenems are the most effective option for nosocomial infections in areas with a high prevalence of extended-spectrum β-lactamase-producing Enterobacteriaceae. Tigecycline may be a potential alternative, although recent studies have showed increased mortality related to its low clinical efficacy and it should not, therefore, be recommended as first-line therapy in the general population [58] . Penicillin used in combination with β-lactamase inhibitors (e.g., piperacilin-tazobactam) may be an adequate alternative.…”
Section: Treatment Of Nosocomial Sbpmentioning
confidence: 99%
“…After the FDA warning several meta-analysis were published; obviously using different methodologies and selecting different studies. Yahav et al [3] meta-analysis reported statistically higher all-cause 30-day mortality in the tigecycline arms. On the other hand, Cai et al [4] found no difference in all-cause mortality and drug-related mortality between tigecycline and the comparators, whereas Tasina et al [5] demonstrated reduced clinical efficacy and increased mortality for tigecycline, but the difference was not statistically significant.…”
mentioning
confidence: 98%
“…On the other hand, analyzed data from non-approved indications showed that the tigecycline arm was statistically less effective. Finally, meta-analyses of study-level data suggested decreased clinical efficacy as a possible explanation for the demonstrated imbalance in mortality [3,8].…”
mentioning
confidence: 99%
“…The cause of the imbalance has not been established. One independent meta-analysis of clinical trial data suggested decreased clinical and microbiological efficacy of tigecycline combined with higher rates of superinfections as explanations [4], while others [5,6] were not able to identify any significant differences in efficacy or microbiologic eradication to account for the results.…”
Section: Introductionmentioning
confidence: 99%